English pronunciation in use - Hancock, Mark. (Cambridge : Cambridge University Press, 2004)
A new edition of our best-selling pronunciation title, now in full colour and with a new section on understanding fast, authentic speech.
CD-ROM mini-guide / Sylvie Donna with Mark Hancock.
CD-ROM for Windows® XP, Vista, 7 and Mac OSX 10.6 or 10.7.
LC copy imperfect: wanting CD-ROM.
Keywords: English language -- Pronunciation by foreign speakers -- Problems, exercises, etc; English language -- Textbooks for foreign speakers -- Problems, exercises, etc; English language -- Spoken English -- Problems, exercises, etc; Listening -- Problems, exercises, etc; English language -- Sound recordings for foreign speakers